Optimization of Tensile Strength in Pineapple Leaf Fiber Composites: A Study of Fiber Volume Fractions with Clear Polyester Resin - Fatimah Zahra; Ferri Safriwardy; Muhammad Habibi; Zulmiardi Zulmiardi; Muhammad Nuzan Rizki (Electronic Journal of Education, Social Economics and Technology, 2025)
The utilization of pineapple leaf fiber is still relatively small, only used as a basic material for various types of furniture products, fabrics for fashion products, crafts and composites as forming materials. This study aims to analyze the tensile strength of pineapple leaf fiber composites with variations in volume fractions using clear polyester resin. In this study, composites were made using three different volume fractions, namely 60% fiber: 40% resin, 70% fiber: 30% resin, and 85% fiber: 15% resin. After the test specimen manufacturing process, the specimens were then tested for tensile strength on each volume fraction. The results of this study indicate variations in tensile strength on each volume fraction used, where using a volume fraction of 85% fiber: 15% resin produces higher tensile strength compared to the volume fraction of 60% fiber: 40% resin and 70% fiber: 30% resin. Pineapple leaf fiber reinforced composites with variations in the volume fraction of pineapple leaf fiber 60%: resin 40%, pineapple leaf fiber 70%: resin 30%, and pineapple leaf fiber 85%: resin 15%. From the percentage variations, the highest tensile strength is in pineapple leaf fiber 85%: resin 15% with an average value of 105.69 MPa, elastic modulus strength of 1571 MPa, and elongation of 6.74%. While the lowest tensile strength value is in pineapple leaf fiber 60%: resin 40%, with an average value of 74.30 MPa, elastic modulus strength of 1231 MPa, and elongation of 6.04%, it can be concluded that the higher the percentage of fiber, the higher the tensile strength value. Variations in the volume fraction of pineapple leaf fiber can affect the mechanical properties of clear polyester resin composites. The composite strength value often increases with the increase in the fiber volume fraction. However, a high fiber volume fraction does not always have a good effect on the strength of the composite. The strength of the composite is not only influenced by the number of fibers but is also influenced by the binding factor, namely the matrix.